If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = 2(2x + 6) Reorder the terms: -2 + 6x = 2(2x + 6) Reorder the terms: -2 + 6x = 2(6 + 2x) -2 + 6x = (6 * 2 + 2x * 2) -2 + 6x = (12 + 4x) Solving -2 + 6x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 6x + -4x = 12 + 4x + -4x Combine like terms: 6x + -4x = 2x -2 + 2x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + 2x = 12 + 0 -2 + 2x = 12 Add '2' to each side of the equation. -2 + 2 + 2x = 12 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 12 + 2 2x = 12 + 2 Combine like terms: 12 + 2 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 2222+m=35 | | 9x-4=5(2x-3) | | 3x+4x=-x+7m | | -1.2y+.8=-.76 | | 7x+1=2(2x+2) | | 44+m=35 | | h(t)=-16t^2+122t+10 | | 6x-1=4(x-1) | | 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) | | 8n-12=40 | | (7+x)/2+3=12 | | 155*22/31*18/25 | | 5a-12=88 | | 9/8*4/5 | | 12-(4m+4)=3+3m-16 | | 2(x-5)+1=-(x+3) | | 7x-24=54 | | -2*(3x-1)-3=-4 | | -0.5x+4.21=0.3x+8.41 |